On Her Own Account: How Strengthening Women’s Financial Control Impacts Labor Supply and Gender Norms - Field, Erica; Pande, Rohini; Rigol, Natalia; Schaner, Simone; Troyer Moore, Charity (American Economic Review, 2021)
Can increasing control over earnings incentivize a woman to work, and thereby influence norms around gender roles? We randomly varied whether rural Indian women received bank accounts, training in account use, and direct deposit of public sector wages into their own (versus husbands') accounts. Relative to the accounts only group, women who also received direct deposit and training worked more in public and private sector jobs. The private sector result suggests gender norms initially constrained female employment. Three years later, direct deposit and training broadly liberalized women's own work-related norms, and shifted perceptions of community norms.